Hypertension Exercise: A Non-Pharmacological Strategy for Reducing Blood Pressure in Adults with Hypertension - Wahdini, Rizqa; Sibualamu, Khalida Ziah; Chairunisa, Ratu (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Hypertension is recognized as a leading contributor to cardiovascular diseases and is frequently labeled a "silent killer" due to its lack of clear symptoms, despite its significant impact on global illness and death rates.  This research aimed to evaluate the influence of such exercise on blood pressure in adults diagnosed with hypertension. A pre-experimental design utilizing a one-group pretest–posttest method was applied, involving 43 participants selected via purposive sampling based on set inclusion criteria. The data were examined using the Shapiro–Wilk test for normality and the Wilcoxon Signed Rank Test for hypothesis testing. Findings revealed that prior to the intervention, the median systolic pressure was 148 mmHg, and the median diastolic pressure stood at 88 mmHg. Following the exercise intervention, the systolic median dropped to 141.75 mmHg and the diastolic to 84 mmHg. Statistical analysis with the Wilcoxon test returned a p-value of 0.000 (below 0.05) for both measures, indicating a statistically significant change post-intervention. These outcomes demonstrate that hypertension exercise can be an effective method for lowering blood pressure in hypertensive adults. The results support the broader adoption of non-drug-based strategies in communities to help manage and control hypertension.